The Living Law’s Restorative Justice: Implementation of Restorative Justice as an Integrative Mechanism in Criminal Law - Henny Saida Flora (Unram Law Review, 2023)
The urgency of this research is the application of local value-based RJ in the community as an integrative mechanism in efforts to resolve disputes or conflicts in the community. This study aims to answer two legal problems, namely: the urgency of implementing RJ by adopting living law in society and the formulation of RJ implementation as an integrative mechanism that adopts living law in society as an effort to settle criminal law. This research is normative legal research by optimizing conceptual and statutory approaches. The results of the study confirm that the urgency of implementing RJ by adopting living law in society is expected so that the criminal justice system in Indonesia can run and be enforced effectively because it is based on living law which originates from people's personalities. The formulation of the application of RJ as an integrative mechanism in the criminal law settlement process is to reform the criminal procedural law through the revision of the Criminal Procedure Code by including the RJ substance which facilitates living law in society. However, because the process of revising the Criminal Procedure Code takes a long time, a transitional legal product can be formed in the form of a SKB RJ which substantially contains the principles, basis and practice of implementing RJ by facilitating living law in society in the criminal justice system.